2022
DOI: 10.1371/journal.pone.0261164
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of life satisfaction among Ghanaians aged 15 to 49 years: A further analysis of the 2017/2018 Multiple Cluster Indicator Survey

Abstract: The inclusion of life satisfaction in government policies as a tracker of the social and economic progress of citizens has been recommended. This has encouraged the scientific investigation of life satisfaction levels of people in tandem with factors responsible for these levels. Only a few studies have attempted to do this in Ghana with mixed findings. This study, therefore, extends previous literature by examining the determinants of life satisfaction among Ghanaians in two ways: a full sample and a gender-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
4
4
0
Order By: Relevance
“…The results of statistical analysis showed that the differences in residents’ life satisfaction in terms of marital status, residence and employment status were statistically significant. These results are consistent with a study by Owusu Ansah et al [ 36 , 37 ]. Owusu Ansah, K. analyzed cross-sectional data, including a sample of 20,059 women and men of ages ranging from 15 to 49 years [ 36 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of statistical analysis showed that the differences in residents’ life satisfaction in terms of marital status, residence and employment status were statistically significant. These results are consistent with a study by Owusu Ansah et al [ 36 , 37 ]. Owusu Ansah, K. analyzed cross-sectional data, including a sample of 20,059 women and men of ages ranging from 15 to 49 years [ 36 ].…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with a study by Owusu Ansah et al [ 36 , 37 ]. Owusu Ansah, K. analyzed cross-sectional data, including a sample of 20,059 women and men of ages ranging from 15 to 49 years [ 36 ]. In his study, marital status, wealth index, and region of residence were found to be significantly correlated with life satisfaction.…”
Section: Discussionsupporting
confidence: 94%
“…This finding contradicts the results of McIntyre et al [ 18 ] and Addai et al [ 34 ], who found that females who were never married were more satisfied than currently and formerly married women. However, our finding is consistent with the results of Owusu et al [ 16 ], Yaya et al [ 17 ] and Botha et al [ 35 ], who also found that married women have higher satisfaction than formerly married women. There may be a reason women previously married and never married undergo constant criticism and bullying from society, hence reduced satisfaction with life.…”
Section: Discussionsupporting
confidence: 93%
“…In developing countries, almost the same factors were significantly associated with life satisfaction. A study in Ghana showed a significant association between age, wealth index, gender, highest education level, marital status, type of residence, and marital status with life satisfaction [ 16 ]. Surprisingly, a study on Malawian people found no significant association between factors wealth index, education level with life satisfaction [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this line, more working hours in mothers have been linked to lower SWFoL in their adolescent children ( 71 ), and self-employed mothers and their adolescents children have reported better diet quality than employed mothers and their adolescents ( 28 ). During the COVID-19 pandemic, changes in adults' life satisfaction has been also associated with the city and region of residence, that is, the likelihood of experiencing decreased life satisfaction is higher for those living in a big city compared to those living in small cities or in rural areas ( 13 , 73 ). However, the moderating role of parent's job-related variables and place of residence on domain and life satisfaction for the individual and their family members remain scarcely explored.…”
Section: Introductionmentioning
confidence: 99%